2020
DOI: 10.1051/0004-6361/201936877
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical modeling of the starless core L 1512

Abstract: Context. The deuterium fractionation in starless cores gives us a clue to estimate their lifetime scales, thus allowing us to distinguish between dynamical theories of core formation. Cores also seem to be subject to a differential N 2 and CO depletion, which was not expected from the models. Aims. We aim to create a survey of ten cores to estimate their lifetime scales and depletion profiles in detail. After describing L 183, located in Serpens, we present the second cloud of the series, L 1512, from the star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 83 publications
(152 reference statements)
4
33
2
Order By: Relevance
“…The values derived from observations are all averages over 5 × 5 pixels centred on point 1. The core temperature is based on the N 2 H + observations by Lin et al (2020). In addition to the models in Table 1, we tested three further modifications to the dust properties.…”
Section: Radiative Transfer Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The values derived from observations are all averages over 5 × 5 pixels centred on point 1. The core temperature is based on the N 2 H + observations by Lin et al (2020). In addition to the models in Table 1, we tested three further modifications to the dust properties.…”
Section: Radiative Transfer Modelsmentioning
confidence: 99%
“…We have chosen the cloud LDN1512 (hereafter L1512) to study and model NIR light scattering and thermal dust emission at FIR wavelengths. The cloud has a simple cometary morphology, is nearby (140 ± 20 pc, Launhardt et al 2013), and based on the reported small line width of N 2 H + (Caselli et al 1995(Caselli et al , 2002Lin et al 2020), appears to be quiescent.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other substitutions cause a minor change in the molecular symmetry, such as 12 C-13 C in C 3 H 2 ; in such cases, the potential energy surface of the interaction is basically unchanged. Significant effects on collisional properties occur mostly for H→D substitutions, especially for hydrides: DCO + -H 2 [138], ND-He [113], ND 3 -H 2 [137], D 2 O-H 2 [85], and N 2 D + -H 2 [139]. If isotopic substitution does not change the symmetry of the molecule at all, the effect on its collisional properties is small (<30%); this category includes 13 CN-H 2 and C 15 N-H 2 [140], and N 15 NH + -H 2 [141] This latter category is the least urgent to update because, for symmetry-conserving isotopic substitutions, simple scaling by (reduced) mass is quite accurate.…”
Section: Planned Updates Of Lamdamentioning
confidence: 99%